The Impact of Mosque-Based Economic Activities on Local Communities: A Case Study in Sarawak - Md Radzi, Mohamad Bazli; Yaacob, Salmy Edawati; Ahmad, Azlin Alisa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The mosque has a comprehensive function covering the spiritual, educational, economic, and social aspects. However, the potential of mosques as centers for economic development within local communities remains underexplored and underutilized. Many mosques lack the strategic framework and resources to effectively implement economic activities that could benefit their communities. This study aimed to examine the impact of economic activities in mosques on the local community. Furthermore, this study also analyzes the implementation of economic activities through Waqf. The qualitative methodology was chosen for this study, where a selection of respondents was made by purposive sampling. Therefore, the sampling involved 20 informants, including officers from the religious Islamic department and a committee from 10 mosques throughout the Sarawak state. These have been identified as actively carrying out economic activities. The list of mosques is derived from the Sarawak Islamic Religious Department. The instruments used for this study are semi-structured interviews and content analysis, whereas the data obtained is analyzed using an atlas.ti software. The finding shows that economic activities at the mosque can be implemented and impact the community. Besides that, waqf helps the mosque enhance its economic activity. The positive impact of the economic activities carried out in the mosque undeniably improves the community's standard of living and increases the mosque’s funds. Moreover, it indirectly attracts more people to come to the mosque.